2019
DOI: 10.3389/fimmu.2019.02435
|View full text |Cite
|
Sign up to set email alerts
|

Cocaine Use Disorder Is Associated With Changes in Th1/Th2/Th17 Cytokines and Lymphocytes Subsets

Abstract: Background: Cocaine is a psychostimulant drug with high addictive proprieties. Evidence suggests that cocaine use leads to critical changes in the immune system, with significant effects on T, B, and natural killer (NK) cells and influencing peripheral levels of cytokines. The presence of abstinence-related symptoms during detoxification treatment is known to influence the prognosis. Here, our aim was to investigate immune profiles in women with cocaine use disorder (CUD) according to withdrawal symptoms sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 63 publications
(77 reference statements)
2
16
0
Order By: Relevance
“…Serum concentrations of IL-4 and IFN-γ both decreased after cocaine and haloperidol treatment; however, due to considerable inter-individual variability, we did not find the effects to be statistically significant. Results suggest that, for some individuals, haloperidol and cocaine may suppress IL-4 and IFN-γ signaling [18,55]. Moreover, the concentrations of IL-4 and IFN-γ that we detected in our study were comparable to that of control groups in other reports [56,57], suggesting that manipulations of chronically implanted catheters per se did not induce pronounced inflammation.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Serum concentrations of IL-4 and IFN-γ both decreased after cocaine and haloperidol treatment; however, due to considerable inter-individual variability, we did not find the effects to be statistically significant. Results suggest that, for some individuals, haloperidol and cocaine may suppress IL-4 and IFN-γ signaling [18,55]. Moreover, the concentrations of IL-4 and IFN-γ that we detected in our study were comparable to that of control groups in other reports [56,57], suggesting that manipulations of chronically implanted catheters per se did not induce pronounced inflammation.…”
Section: Discussionsupporting
confidence: 79%
“…Cocaine suppresses the immune system via both central and peripheral mechanisms [15][16][17][18]. The hypothalamic-pituitary-adrenal (HPA) axis and sympathetic nervous system are the primary pathways through which cocaine modulates the immune system [17,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, no effective medications exist that successfully treat cocaine use disorders (CUDs). Studies in humans have demonstrated that CUDs are associated with altered serum levels of pro-and antiinflammatory cytokines (Moreira et al, 2016;Zaparte et al, 2019). As well, serum cytokine levels may be useful indicators for assessing the severity for CUDs and identifying effective treatment strategies, although sex differences and psychiatric comorbidity are important factors to consider (Araos et al, 2015;Pedraz et al, 2015;Maza-Quiroga et al, 2017;Pianca et al, 2017).…”
Section: Cocainementioning
confidence: 99%
“…In addition, immunological alterations have been observed in individuals with SUD ( Cohen et al, 1993 ; Schuch-Goi et al, 2017 ; Sureshchandra et al, 2019 ; Zaparte et al, 2019 ). Studies showed that alcohol and cocaine/crack abuse increase the risk for infectious diseases ( Butler et al, 2017 ; Collaborators, 2018 ; Halpern et al, 2017 ; Peacock et al, 2018 ; WHO, 2018 ).…”
Section: Introductionmentioning
confidence: 99%